Assessing empathy among undergraduate medical students: a cross sectional analysis using the Jefferson scale in a medical school in Coastal Karnataka - Nair, Suma; Shetty, Ranjitha S.; Guha, Swati; Anjum, Zari; Kamath, Asha (International Journal Of Community Medicine And Public Health, 2018)
Background: Empathy has been shown to improve the physician’s diagnostic skills as well as enhance the quality of communication with the patient. Empathy being an integral component of patient care, this study was designed to measure empathy levels among undergraduate medical students and to identify the factors associated with it in this population. Methods: This cross sectional study was carried out among 437 medical students including interns on the rolls of a medical school in coastal Karnataka. The students were administered a psychometrically validated Jefferson Scale of Empathy–Student Version (JSE-S) questionnaire, to measure various components of empathy. Responses were indicated on a seven point Likert scale and total scores ranged from 20–140, with higher values indicating higher levels of empathy. Results: Mean empathy score among the participants was 100.5±14.8, with significantly higher score being reported by females than males [101.9 vs. 97.3, p=0.002] and by first year students compared to third year students [105.2 vs. 95.3, p<0.01]. Empathy scores showed a declining trend as the students progressed through the medical school (p=0.002). Conclusions: Although the study showed higher empathy level among female medical students, there appeared a declining score among both genders as the years of study progressed with a marginal increase during the internship phase. This necessitates the need for incorporating caregiving as an integral part of the medical school curriculum by stressing on doctor- patient communication skills, which in turn could aid medical students become compassionate physicians.